Diurnal UT Variation of Low Latitude Geomagnetic Storms Using Six Indices. Issue 10 (22nd October 2021) - Balan, N.; Ram, S. Tulasi; Manu, V.; Zhao, Lingxin; Xing, Zan‐Yang; Zhang, Qing‐He
Abstract: A quasi‐semidiurnal type pattern was observed earlier in the diurnal UT variation of the geomagnetic storms studied using mainly Kyoto Dst (disturbance storm‐time) index. However, the pattern has been argued as apparent due to uneven longitude distribution of the four Dst observatories. Unlike earlier studies, this paper investigates the diurnal UT variation of the storms automatically identified in six available indices including Kyoto Dst, USGS (United States Geological Survey) Dst, SymH (symmetric‐H), RC (ring current), Dcx (corrected extended Dst), and AER (Atmospheric and Environmental Research) in 50, 50, 36, 21, 5, and 7 years, respectively. The indices are derived using 4, 4, 12, 14, and 15 ground observatories (with maximum longitude separations of ∼120°, 120°, 70°, 110°, and 50°) and four DMSP (Defense Meteorology Satellite Program) satellites, respectively. The UT distribution of the storm intensity (minimum value of an index during the storm main phase) in all indices shows a striking quasi‐semidiurnal type variation with maxima around 06–08 UT and 21–23 UT and minima around 03–05 UT and 13–15 UT. Similar quasi‐semidiurnal variation is also observed in the computed values of the main energy input in the ring current. The variation correlates well with the variations of the dipole tilt angles μ and θ involved in the equinoctial hypothesis and Russell‐McPherron (RM) effect, respectively. These observations indicate that the quasi‐semidiurnal variation is real. Plain Language Summary: Large disturbances in the geomagnetic field lasting form several hours to several days are known as geomagnetic storms. The variations of the occurrence and intensity of the storms with solar activity and season have been understood thanks to the works of a large number of scientists. The variation of the storms with the time‐of‐day studied using mainly the low latitude geomagnetic activity index Dst has shown a quasi‐semidiurnal pattern. The pattern, however, has been argued as apparent due to the uneven longitude distribution of the four magnetic observatories used for deriving Dst. The present study investigates the diurnal UT variation of the storms using six available indices. The results show similar striking quasi‐semidiurnal patterns in the UT distribution of the storm intensity in all indices and computed value of the main energy input in the ring current. The quasi‐semidiurnal pattern also correlates well with the angles μ and θ involved in the mechanisms of equinoctial hypothesis and RM effect. These observations indicate that the quasi‐semidiurnal variation is real. Key Points: A striking quasi‐semidiurnal pattern is observed in the UT distribution of the geomagnetic storm intensity in six low latitude indices Similar pattern exists in the UT variation of the computed value of the main energy input in the ring current The quasi‐semidiurnal pattern correlates well with the angles μ and θ involved in the mechanisms of equinoctial hypothesis and RM effect